Is Growth-friendly Surgical Treatment Superior to One-stage Posterior Spinal Fusion in 9- to 11-year-old Children with Congenital Scoliosis? - Xu, Liang; Sun, Xu; Du, Changzhi; Zhou, Qingshuang; Shi, Benlong; Zhu, Zezhang; Qiu, Yong (Clinical orthopaedics and related research, 2020)
The distraction-based growth-friendly technique has become a mainstay of treatment for young children with long-spanned congenital scoliosis. However, in patients who are 9 years to 11 years old, the choice is much less clear, and posterior spinal fusion is also a potential option. Comparing growth-friendly scoliosis surgery and posterior spinal fusion, which technique (1) provides greater correction of spinal deformity, (2) is associated with more surgical complications, and (3) results in greater improvement in pulmonary function tests, health-related quality of life scores, other patient-reported outcomes? Between 2009 and 2017, one spinal center performed 212 spinal interventions for scoliosis in patients aged between 9 years and 11 years old and who had open triradiate cartilage, including 40 patients with growth-friendly approaches (34 with growing-rod technique and six with a vertical expandable prosthetic titanium rib) and 172 with one-stage posterior spinal fusion, respectively. During this period, our general indications for using growth-friendly surgery were patients with open triradiate cartilage, major curve higher than 40°, and upper and lower end vertebrae involving at least eight segments. Twelve patients with a median (range) age of 9.3 years (9 to 11) treated with growth-friendly surgery met the following inclusion criteria: (1) had at least two lengthening procedures before definitive spinal fusion along with 2 years of follow-up after definitive spinal fusion; (2) had been followed until skeletal maturity (Risser grade ≥ 4); and (3) with complete radiographic and clinical data (health-related quality of life (HRQoL) and pulmonary function test results) preoperatively and at the latest follow-up. A group of patients between 9 years and 11 years old and underwent one-stage posterior spinal fusion was selected from our database of patients with congenital scoliosis. Our general indications for using one-stage posterior spinal fusion were patients with a major curve greater than 40°, and with thoracic height higher than 18 cm. Sixty-two patients who had open triradiate cartilage and had been followed until skeletal maturity (Risser grade ≥ 4) were accounted for. In this retrospective, controlled study, we matched patients in the posterior spinal fusion group to those 12 patients who had growth-friendly surgery by age, sex, pathologic findings, major curve size, and location of the apex of the major curve (2:1 matching provided 24 patients in the control group). The median (range) age was 9.8 years (9 to 11). We then compared the groups in terms of magnitude of correction and postoperative complications. Surgical complications, including infection, implant-related complications, and alignment-related complications were evaluated and classified using the surgical complications grading system. Pulmonary function tests and HRQoL were also compared between groups. Pulmonary function tests were performed at the same center with a spirometer. HRQoL were assessed by questionnaire, including the 24-item Early-onset Scoliosis questionnaire for parent-reported outcomes and the Scoliosis Research Society-22 questionnaire for patient-reported outcomes. All patients involved in this study gave their informed consent. The posterior spinal fusion group achieved a greater correction magnitude at the latest follow-up (median [range] 46% [28 to 70] versus median 34% [9 to 58], difference of medians = 11%; p < 0.001) than the growth-friendly group. A higher proportion of patients in the growth-friendly group had complications than in the posterior spinal fusion group (7 of 12 versus 4 of 24; p = 0.03). There were no between-group differences in terms of pulmonary function tests. Few differences were found between the groups in terms of 24-item Early-onset Scoliosis parental impact (median [range] 60 [44 to 83] for the growth-friendly group versus median 71 [55 to 87] for the posterior spinal fusion group, difference of medians = 13; p = 0.001), financial burden (median 44 [30 to 55] for the growth-friendly group versus median 62 [53 to 75] for the posterior spinal fusion group, difference of medians = 16; p < 0.001) and the Scoliosis Research Society-22 self-image scores (median 3.8 [3.2 to 4.3] for the growth-friendly group versus median 4.4 [4.1 to 4.6] for the posterior spinal fusion group, difference of medians = 0.5; p = 0.006) at the latest follow-up, and those differences that were observed all favored the posterior spinal fusion group. In light of the superior deformity correction and fewer observed complications with posterior spinal fusion, and the absence of important differences in validated outcomes scores or pulmonary function tests, posterior spinal fusion might be a better choice for 9- to 11-year-old children with long-spanned congenital scoliosis and limited growth potential in the intended instrumentation area. Level III, therapeutic study.